Singing with elephants - Engle, Margarita (Viking, 2022)
Lonely Cuban-born eleven-year-old Oriol lives in Santa Barbara, California, where she enjoys caring for injured animals, but her budding friendship with Gabriela Mistral, the first Latin American winner of a Nobel Prize in Literature, emboldens Oriol, an aspiring writer, to open up and create a world of words for herself.